Dialogue Summary: Preventing Interpersonal and Self-directed Violence and Injuries in the Caribbean - Ciurea, Ileana; Moat, KA; Yearwood, Andrea C. (My University, 2015)
A summary of what was learned from a stakeholder dialogue that addressed problems related to violence and injuries prevention, options for addressing these problems, key implementation considerations, and next steps for preventing interpersonal and self-directed violence and injuries in the Caribbean.
Keywords: violence; injuries; Caribbean; prevention